The best American magazine writing 2016 - Holt, Sid (Columbia University Press, 2016)
Features articles that were judged finalists and winners in the National Magazine Awards, presenting works from leading journalists on such topics as reparations, Internet sexual harassment, the public humiliation complex, and the college rape crisis.
Keywords: American prose literature -- 21st century.; Journalism -- Awards -- United States.; Prose américaine -- 21e siècle.; LANGUAGE ARTS & DISCIPLINES -- Journalism.; American prose literature; Journalism -- Awards; United States; 2000-2099